LARANGAN BAGI PEREMPUAN HAID MELAKUKAN AKTIFITAS DI MESJID DAN MEMBACA AL-QUR’AN: Kajian Hadis Tematik - Duhriah Duhriah (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Mosque is a holy place that is used for performing worship and religious activities. The activities that are performed at the mosque contain rich positive value besides religious value and blessing. Today, mosque is not only a place for worship but also as a multifunctional area such as a place for preaching, a place for teaching and learning for moslem generation. However, this place benefit could not be obtained by every moslem, for example menstruating women. There are some verses in Islamic teach that bans for menstruating women to have activities at the mosque that implicitly says that these women are not able to do any activities at the mosque. On the other hand, there are also verses that allow women to do so. These verses also say about prohibition of reciting Qur’an for menstruating women